ð˜”ð˜¦ð˜ð˜°ð˜ªð˜¥ð˜°ð˜¨ð˜ºð˜¯ð˜¦ ð˜¥ð˜¦ð˜¤ð˜¢ð˜ð˜ªð˜¯ð˜¦ð˜¢ð˜µð˜¢ PARASITA CAFEEIROS NA ILHA DE SÃƒO TOMÃ‰ - Lordello, Rubens R. A.; Fazuoli, Luiz Carlos (REVISTA DE AGRICULTURA, 2020)
ð˜”ð˜¦ð˜ð˜°ð˜ªð˜¥ð˜°ð˜¨ð˜ºð˜¯ð˜¦ ð˜¥ð˜¦ð˜¤ð˜¢ð˜ð˜ªð˜¯ð˜¦ð˜¢ð˜µð˜¢ PARASITA CAFEEIROS NA ILHA DE SÃƒO TOMÃ‰